(untitled) (Global Journal of Human-Social Science, 2016)
The world as a global village has witnessed quantum leap in areas of science and technology With great impacts in travel communication information and media industrialization and mechanization man has found it very easy to achieve great task within a limited scope of time This has given man a big relief as task that formally took man months and years to achieve are being met within a short period of time With improvements in information technology globalization has increased The world is brought closer and the world s economy is quickly becoming a single interdependent system Information can be shared quickly and easily from all over the globe and barriers of linguistic and geographic boundaries can be torn down as people share ideas and information with each other Communication has become an easier cheaper and faster system with the help of information technology Using the internet people can speak to each other all over the world using video conferencing With these great impacts made in the area of information and its corresponding ills it becomes necessary to evaluate the concept of information technology as it affects our learning system This articles centers on the importance of information technology however it pays particular attention to the relation that exists between ICT and Academic Libraries This approaches thus exposes the positive and negative impacts of the ICT to learning process and goes on to suggest ways to enhancing a better understanding and use of the ICT in our academic libraries